Molecular identification of lactic acid bacteria SR6 strain and evaluation of its activity as an anticancer in T47D cell line - Ida Bagus Ngurah Swacita; I. Wayan Suardana; I. Gusti Ngurah Sudisma; Hevi Wihadmadyatami (Veterinary World, 2022)
Background and Aim: Breast cancer is the most common type of cancer in women because it attacks the productive age. Preliminary studies showed that lactic acid bacteria (LAB) strain SR6 from the Bali cattle colon has the potential to act as a superior probiotic. It is also assumed that its bacteriocin structure is specific and has a strong relationship with the specificity of the ligand and its biological activity at a receptor. Therefore, this study aims to assess the use of local LAB strains, which produce bacteriocins as anticancer agents, as well as to identify the bacteria as potent producers molecularly.